Time-dependent multiple barriers of the electric and exchange fields in silicene-like nanoribbons. (10th September 2018) - Shao, Lin; Xu, Hengyi; Xu, Ning
Abstract: We study the transport properties of the silicene nanoribbons subject to periodically driving electric and exchange fields. The multiple barriers made up of corresponding fields reshape the DC conductance by imposing pronounced both Fabry–Perot- and Fano-type resonances accompanied with high spin polarizations. In particular, a transport gap can be generated by the electric barriers with an appropriate strength, which is absent in the case of the barriers of the exchange field. The effects of the hybrid barriers including both electric and exchange fields, however, are not simply a mixture of two individual barriers, while depend on the relative phase of the time-varied barriers. In contrast to static barriers, the further studies of the driving frequency indicate that the in-gap states can survive in the transport gap for electric barriers as the frequency increases. This feature is particularly valuable for building spin-filter or spin-switcher devices.